A novel electrocatalytic system with high reactive chlorine species utilization capacity to degrade tetracycline in marine aquaculture wastewater. (August 2022) - Ni, Ting; Feng, Haopeng; Tang, Jing; Wang, Jiajia; Yu, Jiangfang; Yi, Yuyang; Wu, Yangfeng; Guo, Yuyao; Tang, Lin
Abstract: The problems of high salinity and coexistence of antibiotics in mariculture wastewater pose a great challenge to the traditional wastewater treatment technology. Herein, an electrocatalytic system based on cathodes to sustain reactive chlorine species (RCS) in a high chlorine environment was proposed. The results show that the content of RCS is affected by cathodes. The electrocatalytic system with FeNi/NF as cathode has the largest RCS retention capacity when compared with other cathode systems (carbon felt, nickel foam, copper foam, stainless steel, and nickel-iron foam). This is related to FeNi/NF's higher hydrogen production activity, which inhibits the reduction reaction of RCS. Furthermore, the degradation of tetracycline by the proposed FeNi/NF system maintained long-term effective performance across 20 cycles. Thus, the application of high chlorine resistance electrocatalysis system provides a possibility for practical electrocatalysis treatment of mariculture wastewater. Graphical abstract: Image 1 Highlights: The FeNi/NF-system showed ultrahigh durability and activity in a NaCl environment. Abundant RCS preserved in the FeNi/NF-system promotes tetracycline's degradation. FeNi/NF's higher HER activity inhibits the reduction reaction of RCS. Weakening RCS's reduction by cathodes can improve the electrocatalytic activity.